HUBUNGAN BEBAN KERJA DENGAN BURNOUT SYNDROME PADA PERAWAT KAMAR OPERASI - Ruthari, Danis (Media Husada Journal Of Nursing Science, 2025)
The existence of a surgical schedule that exceeds the hospital capacity, causing operating room nurses to overtime. One of the impacts of this overtime is the nurse's workload. High workload can make someone stressed. The aims of this study was to determine interaction between workload and  burnout syndrome. This study is observational analytic study with a cross-sectional approach, using a total sampling technique with 50 respondents. The research instrument used a questionnaire sheet to measure workload and burnout syndrome. Data analysis with the Spearman Rank correlation test with SPSS IBM Version 23. The results showed that most of the 29 respondents (58%) had a light workload and most of the 41 respondents (82%) had light burnout syndrome. The results of the Spearman Rank statistical test obtained a p value = 0.000, with a positive direction and a correlation coefficient value of 0.623 which indicates that the relationship between the two variables is strong, which can be concluded that there is a significant relationship between workload and burnout syndrome for nurses in the Central Surgery Installation of Dr. Saiful Anwar Hospital.. Nurses with a workload that is too high and does not match their abilities can cause fatigue or burnout syndrome. Nurses need to pay attention to and implement working hours and rest times in accordance with applicable regulations. In addition, nurses are also expected to be able to maintain good working relationships with superiors, coworkers and patients so that they can prevent stressors from the environment.